KEWENANGAN PENGADILAN DALAM PENYELESAIAN SENGKETA KEPEMILIKAN PT. TELEVISI PENDIDIKAN INDONESIA (PT. TPI) YANG MEMUAT KLAUSUL ARBITRASE (Studi Kasus Putusan Nomor 238 PK/Pdt/2014) - Pangaribuan, Citra Bakti (JURNAL MERCATORIA, 2016)
The existence ofthe arbitration clause in an agreement to hold the rights of the parties to submit the settlement of disputes to the Court. District Court was not authorized to adjudicate disputes which the parties have been bound in the arbitration agreement. District Courtmust reject and will not intervene in the dispute resolution in case established through arbitration. Similarly,`regarding a dispute that has been set by arbitration. Likewise ,a dispute concerning the ownership of PT. Televisi Pendidikan Indonesia where in the investment treaty arbitration agreement contained arbitration clause. This research study of its kind to examine the application of normative juridical and this research is descriptive analytical. Over ownership of PT. Televisi Pendidikan Indonesia (TPI) is in the field of traded is putes that there klausula arbitration. The parties in writing to the treaty have included the arbitrationas a dispute resolution forum for that in this case the attitude of the court that received the settlement of disputes ownership of PT. Televisi Pendidikan Indonesia (PT. TPI) has violated the provisions of Law No.30 of 1999 on arbitration and alternative dispute resolut